A social neuroscience perspective on maize input-use decisions: a grounded theory study from Bengkayang, West Kalimantan, Indonesia - Pepi Rospina Pertiwi; Bayu Eka Wicaksana; Ludivica Endang Setijorini; Heny Kurniawati; Erika Pradana Putri; Ismail Hasvi; Anita Suharyani; Sawitania Situmorang (Journal of Agricultural Socio-Economics (JASE), 2026)
Maize plays a strategic role in Indonesia’s food security; however, productivity disparities persist despite the availability of production inputs, indicating that farmers’ decisions are shaped not only by technical factors but also by behavioral processes. Existing studies predominantly emphasize physical and economic determinants while overlooking the sociocognitive and affective dimensions underlying farmers’ behavior. Unlike previous studies that rely on linear behavioral frameworks such as the Theory of Planned Behavior, this study adopts a social neuroscience perspective integrated with an inductive grounded theory approach to examine the interaction of cognitive, affective, and social processes in farmers’ input-use decisions. This study employed a qualitative grounded theory design using in-depth, semi-structured interviews with 10 maize farmers in Bengkayang Regency, West Kalimantan, Indonesia, selected through iterative snowball sampling until theoretical saturation (at Participant 3) and conceptual saturation (at Participant 10) were achieved. Data were analyzed using the constant comparative methods, including open, axial, and selective coding. The findings reveal that farmers’ input-use decision-making is shaped by a “relational-collective survival-oriented rationality,” in which decisions are guided not only by individual profit maximization, but also by the need to maintain their social relationships, relational trust, collective security, and livelihood continuity to embrace the uncertainty. These behavioral patterns reflect the interaction of cognitive evaluation, affective regulation, and socially embedded experiences associated with the prefrontal cortex, limbic system, and social brain functions, implying the need for more relational and participatory development approaches.